The Statistical Production Function - Smith, Victor E. (Quarterly Journal of Economics, 1945)
Introduction: experimental determination of a theoretical production function, 543. — Imperfect markets and disequilibrium situations, 546. — Delayed adjustments, 548. — Other reasons why actual observations will not show adjustments envisaged by static equilibrium theory, 548. — Functions based upon short-run adjustments, 549. — Transitions, 550. — Time-series and cross-section studies, 551. — Homogeneity, 552. — The data as measurements: industries vs. firms, 553; factors of production, 553; capital, 554; depreciation, 556; sampling, 560. — Conclusion, 562.